2020
DOI: 10.1038/s41598-020-80429-4
|View full text |Cite
|
Sign up to set email alerts
|

The implication of the air quality pattern in South Korea after the COVID-19 outbreak

Abstract: By using multiple satellite measurements, the changes of the aerosol optical depth (AOD) and nitrogen dioxide (NO2) over South Korea were investigated from January to March 2020 to evaluate the COVID-19 effect on the regional air quality. The NO2 decrease in South Korea was found but not significant, which indicates the effects of spontaneous social distancing under the maintenance of ordinary life. The AODs in 2020 were normally high in January, but they became lower starting from February. Since the atmosphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…These COVID-19 lockdowns have caused significant reductions in human activities and traffic worldwide. As human activities have reduced, air quality has improved significantly worldwide (Bauwens et al, 2020;Goldberg et al, 2020;Huang and Sun, 2020;Jin et al, 2020;Koo et al, 2020;Liu et al, 2020;Morales-Solís et al, 2021;Naeger and Murphy, 2020;Oo et al, 2021;Represa et al, 2021). However, some studies found air quality has not improved as we expected or even worsened in some cities due to the complicated atmospheric chemistry, meteorological conditions, and emissions, even anthropogenic emissions from human activities and traffic have reduced significantly (Bekbulat et al, 2021;Chen et al, 2020;Le et al, 2020;Schiermeier, 2020;Shi and Brasseur, 2020).…”
Section: Introductionmentioning
confidence: 89%
“…These COVID-19 lockdowns have caused significant reductions in human activities and traffic worldwide. As human activities have reduced, air quality has improved significantly worldwide (Bauwens et al, 2020;Goldberg et al, 2020;Huang and Sun, 2020;Jin et al, 2020;Koo et al, 2020;Liu et al, 2020;Morales-Solís et al, 2021;Naeger and Murphy, 2020;Oo et al, 2021;Represa et al, 2021). However, some studies found air quality has not improved as we expected or even worsened in some cities due to the complicated atmospheric chemistry, meteorological conditions, and emissions, even anthropogenic emissions from human activities and traffic have reduced significantly (Bekbulat et al, 2021;Chen et al, 2020;Le et al, 2020;Schiermeier, 2020;Shi and Brasseur, 2020).…”
Section: Introductionmentioning
confidence: 89%
“…Visibility is another well-known indicator of aerosol pollutions [33]. Ozone and NO 2 can show the local photochemical activity [34] and atmospheric chemical conditions related to the aerosol pollutions [35,36].…”
Section: Methodsmentioning
confidence: 99%
“…The antiviral mechanisms of digoxin and other cardiac glycosides are through inhibiting the synthesis of viral proteins, blocking the viral life cycle, inhibiting pre-mRNA splicing, inhibiting the synthesis of structural proteins, and inhibiting entry of coronaviruses by blocking endocytosis (Lu et al 2016 ; Amarelle and Lecuona 2018 ). In SARS-CoV-2 infection, cardiac glycosides including digoxin and ouabain have potent in vitro killing of SARS-CoV-2 more than 99% compared to negative control and chloroquine (Cho et al 2020 ). Digoxin had antiviral and anti-inflammatory effects against SARS-CoV and MERS-CoV through inhibition of mRNA transcription, protein translation, and release of viral particles (Burkard et al 2015 ).…”
Section: Anti-heart Failure Drugs and Covid-19mentioning
confidence: 99%